Intended hydration strategies and knowledge of exercise-associated hyponatraemia in marathon runners: A questionnaire-based study - Leggett, T.; Williams, J.; Daly, C.; Kipps, C.; Twycross-Lewis, R. (Journal of Athletic Training, 2018)
Context: Exercise-associated hyponatremia (EAH) is a potentially fatal condition that can be prevented by avoiding excessive fluid intake. Running has become more popular in recent years, so it is important to assess the safety of runners' hydration strategies.